2019
DOI: 10.1016/j.aprim.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de la hiperglucemia con fármacos no insulínicos en pacientes adultos con diabetes tipo 2

Abstract: ResumenEl adecuado tratamiento de la diabetes mellitus tipo 2 (DM2) incluye la alimentación saludable y el ejercicio (150 min/semana) como pilares básicos. Para el tratamiento farmacológico, la metformina es el fármaco de elección inicial, salvo contraindicación o intolerancia; en caso de mal control, se dispone de 8 familias terapéuticas (6 orales y 2 inyectables) como posibles combinaciones. Se presenta un algoritmo y unas recomendaciones para el tratamiento de la DM2. En prevención secundaria cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
5
0
3
Order By: Relevance
“…Apart from the CVD benefit, other guidelines also focus on weight reduction and restrict their use exclusively to patients with high body mass index (BMI) [17]. Yet other guidelines offer a combined approach and advise use of GLP-1 RAs in patients with CVD and/or high BMI [2,[18][19][20]. Guidelines in Spain underscore that the adequate treatment of T2D requires a simultaneous approach to HbA1c, overweight/ obesity, and other CV risk factors such as hypertension, dyslipidaemia or smoking, and highlight that the presence of CVD is a determinant factor for treatment selection [2,21,22].…”
Section: Plain Language Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the CVD benefit, other guidelines also focus on weight reduction and restrict their use exclusively to patients with high body mass index (BMI) [17]. Yet other guidelines offer a combined approach and advise use of GLP-1 RAs in patients with CVD and/or high BMI [2,[18][19][20]. Guidelines in Spain underscore that the adequate treatment of T2D requires a simultaneous approach to HbA1c, overweight/ obesity, and other CV risk factors such as hypertension, dyslipidaemia or smoking, and highlight that the presence of CVD is a determinant factor for treatment selection [2,21,22].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Additionally, these studies showed that the time since diagnosis of diabetes to initiation of GLP-1 RAs was greater than 9 years, reflecting long-standing and probably poorly controlled diabetes [28,32]. This is also reflected in the fact that GLP-1 RAs are often used in combination with other glucose-lowering medication such as metformin, insulin, sodium-glucose cotransporter 2 (SGLT2) inhibitors, and sulfonylureas [28], suggesting that they are used in later phases of diabetes and not mainly after metformin, as suggested by guidelines [2,[18][19][20].…”
Section: How Are Glp-1 Ras Being Used In Spain?mentioning
confidence: 99%
“…Uno de los retos en el tratamiento de la diabetes mellitus tipo 2 (DM2), en general, y en el tratamiento con insulina especialmente, es evitar la hipoglucemia 1 , siendo esta una complicación propia del tratamiento que ofrecemos y no de la enfermedad.…”
Section: Tipos De Insulina Basalunclassified
“…Some general principles, such as avoiding hypoglycaemia, focusing on cardiovascular prevention, individualising control targets, assessing therapeutic adherence, avoiding therapeutic inertia, acknowledging the importance of patient-perceived outcomes (e.g., weight loss), and considering patients' preferences and values, should be considered when treating patients with T2D [43].…”
Section: Visual Patient Assessment Checklist and Prescribing Tips By ...mentioning
confidence: 99%